2016
DOI: 10.1080/15222055.2016.1185068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Substrate Properties for Settlement of Caribbean Staghorn Coral Acropora cervicornis Larvae in a Land‐Based System

Abstract: Stony coral culture has recently been the focus of increasing interest and effort, with most production taking place by asexual reproduction through fragmentation. In corals grown for reef restoration, techniques for sexual propagation offer the potential to increase genetic diversity of species for which this is a concern. After decades of population decline, the Caribbean staghorn coral Acropora cervicornis was listed as threatened under the U.S. Endangered Species Act in 2006, along with its congener, elkho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…However, even though substrate conditioning is known to encourage settlement (Erwin et al, 2008), in the experiment with coatings with combinations of properties, it should also be noted that none of the substrates used in the O. annularis and O. faveolata experiments were conditioned; hence no biofilm could have formed at their surfaces, yet larvae settled successfully, which means that conditioning is unnecessary for these substrates. This represents an advantage over other substrates (Harrison & Wallace, 1990;Patterson et al, 2016;Petersen et al, 2005) that require conditioning prior to larval settlement. However, for the experiment with coatings with a single property, we found that the settlement of O. faveolata was greater on conditioned substrates; this may indicate that these substrates with a single property are not attractive enough on their own to larvae and require conditioning to generate an adequate settlement cue for coral larvae.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though substrate conditioning is known to encourage settlement (Erwin et al, 2008), in the experiment with coatings with combinations of properties, it should also be noted that none of the substrates used in the O. annularis and O. faveolata experiments were conditioned; hence no biofilm could have formed at their surfaces, yet larvae settled successfully, which means that conditioning is unnecessary for these substrates. This represents an advantage over other substrates (Harrison & Wallace, 1990;Patterson et al, 2016;Petersen et al, 2005) that require conditioning prior to larval settlement. However, for the experiment with coatings with a single property, we found that the settlement of O. faveolata was greater on conditioned substrates; this may indicate that these substrates with a single property are not attractive enough on their own to larvae and require conditioning to generate an adequate settlement cue for coral larvae.…”
Section: Discussionmentioning
confidence: 99%
“…13) Soil Texture: Soil texture is essential during the pond construction, and the land should meet the technical requirements [24], [25] that the ideal texture for aquaculture includes clay, loam, and sandy. Furthermore, it helps grow natural food because it contains clay and sand, facilitating high oxygen circulation in the soil [26]. The analysis showed sandy loam soil texture on all transects, including the texture lacking the requirements for aquaculture land.…”
Section: ) Potassiummentioning
confidence: 97%
“…Thus, improving grow-out methods for sexual recruits in land-based nurseries is becoming increasingly relevant to the active restoration of A. cervicornis and maintenance of genetic diversity in out-planted populations (Hunt and Sharp, 2014). Although there is still much to be learned, the improvements made toward the process of collecting wild spawn and settling Acropora larvae in aquaria are substantial (Chamberland et al, 2015(Chamberland et al, , 2016Patterson et al, 2016). Increased settlement and higher survival rates mean more corals to care for and a higher cost to do so in land-based nurseries.…”
Section: Introductionmentioning
confidence: 99%